2017
DOI: 10.18865/ed.27.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Community Partners in Care: 6-Month Outcomes of Two Quality Improvement Depression Care Interventions in Male Participants

Abstract: Objective: Limited data exist on approaches to improve depression services for men in under-resourced communities. This article explores this issue using a sub-analysis of male participants in Community Partners in Care (CPIC).Design: Community partnered, cluster, randomized trial.Setting: Hollywood-Metropolitan and South Los Angeles, California. Participants: 423 adult male clients with modified depression (PHQ-8 score≥10).Interventions: Depression collaborative care implementation using community engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Prior secondary analyses of subgroups within the larger CPIC study sample confirmed that some effects observed for the sample as a whole also applied to key subgroups (gender subgroups and individuals with serious mental illness; Castillo et al, 2018;Mehta et al, 2017;Ngo et al, 2016). The CPIC study has not yet explored intervention effects for those with comorbid depression and anxiety.…”
mentioning
confidence: 90%
“…Prior secondary analyses of subgroups within the larger CPIC study sample confirmed that some effects observed for the sample as a whole also applied to key subgroups (gender subgroups and individuals with serious mental illness; Castillo et al, 2018;Mehta et al, 2017;Ngo et al, 2016). The CPIC study has not yet explored intervention effects for those with comorbid depression and anxiety.…”
mentioning
confidence: 90%